1998
DOI: 10.1111/j.1600-0404.1998.tb07378.x
|View full text |Cite
|
Sign up to set email alerts
|

CAG repeat expansions in patients with sporadic cerebellar ataxia

Abstract: CAG repeat expansions cause spinocerebellar ataxia type 1 (SCA1), SCA2, SCA3, SCA6 and dentatorubral-pallidoluysian atrophy (DRPLA). So far these expansions have been examined mainly in ataxia patients with a family history. However, some sporadic cases with SCA have recently been reported. To elucidate the frequency and characteristics of sporadic SCAs, we screened 85 Japanese ataxia patients without a family history for the SCA1, SCA2, SCA3, SCA6 and DRPLA mutations. As a result, 19 patients (22%) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
4
23
0
Order By: Relevance
“…Thus, further family analysis of these patients with sporadic disease is needed. Consistent with previous reports, 37,40,49 the frequency of sporadic SCA6 was higher than that of the other subgroups. This result suggests that the analysis of SCA6 may further contribute to the genetic classification of patients with autosomal dominant cerebellar ataxia, including patients without a clear family history of the disease.…”
Section: Commentsupporting
confidence: 94%
“…Thus, further family analysis of these patients with sporadic disease is needed. Consistent with previous reports, 37,40,49 the frequency of sporadic SCA6 was higher than that of the other subgroups. This result suggests that the analysis of SCA6 may further contribute to the genetic classification of patients with autosomal dominant cerebellar ataxia, including patients without a clear family history of the disease.…”
Section: Commentsupporting
confidence: 94%
“…Within Germany, there is a cluster of SCA6 families in Westphalia (Riess et al 1997), which is most likely caused by a founder effect (Dichgans et al 1999). Similar to our study, the SCA6 mutation has been found in 13% of apparently idiopathic ataxia patients in Japan (Futamura et al 1998). In contrast, SCA6 has been demonstrated in only 1.5% of sporadic ataxia patients from the US (Moseley et al 1998).…”
Section: Discussionsupporting
confidence: 80%
“…Detection of SCA6 patients beyond H-CCA would be important for future treatment. A majority of authors recommend genetic testing for CAG repeats within CACNL1A4 even in patients with sporadic ataxia [26, 31, 32, 33]. For the efficient screening of SCA6, we would propose testing of CAG repeat expansion in CACNL1A4 in patients having one of the following symptoms: (1) horizontal or oblique gaze nystagmus on physical examination, (2) pure cerebellar atrophy on MRI, even if occurrence is sporadic.…”
Section: Discussionmentioning
confidence: 99%